Fluorescent nanoprobe prepared from hyaluronic acid modified iron selenide nanoparticles for real-time detection of hyaluronidase as tumor marker - Chaoqun Zhang; Jie Song; Xin Shen; Qian Li; Feng Su; Suming Li (Journal of Pharmaceutical and Biomedical Analysis Open)
abstract: A highly sensitive nanoprobe HAPPF@FeSe2NPs was developed for real-time detection of hyaluronidase (HAase) as tumor marker. Hyaluronic acid (HA) was first functionalized with adipic acid dihydrazide (ADH) via amide formation. Carboxyl-terminated polylactide (PLA) was then grafted to HA-ADH using EDC/NHS as coupling agents, yielding an HA-ADH-PLA (HAP) graft copolymer. Iron selenide nanoparticles (FeSe2NPs) were surface coated with HAP by ultrasonic assisted self-assembly. Finally, the resulted HAP@FeSe2NPs were surface-modified with fluorescein isothiocyanate (FITC) and polyethyleneimine (PEI) to obtain HAPPF@FeSe2NPs fluorescent nanoprobe. Analyses by FTIR, XRD, XPS, EDX, TEM, DLS, 1H NMR and TGA confirmed the successful synthesis of the nanoprobe, and fluorescence spectroscopy proved its good detection performance. Moreover, cell imaging results demonstrated the ability of the nanoprobe to target tumor cells. MTT assay and hemolysis tests confirmed its good cyto- and hemo-compatibility. Therefore, it is concluded that HAPPF@FeSe2NPs nanoprobe could be used in targeted tumor cell imaging for early diagnosis of cancers.